Chemical identification and its quality assurance - Milman, Boris L. (Springer, 2011)
This is the first book to show how to apply the principles of quality assurance to the identification of analytes (qualitative chemical analysis). After presenting the principles of identification and metrological basics, the author focuses on the reliability and the errors of chemical identification. This is then applied to practical examples such as EPA methods, EU, FDA, or WADA regulations. Two whole chapters are devoted to the analysis of unknowns and identification of samples such as foodstuffs or oil pollutions. Essential reading for researchers and professionals dealing with the identification of chemical compounds and the reliability of chemical analysis.